The Risk Matrix of Occupational Health and Safety on Cleaning Service Occupation in Universitas X Ponorogo - Aisy Rahmania (Medical Technology and Public Health Journal, 2023)
The risk matrix can be discovered by first identifying the hazards at the work stages. The cleaning service occupation has a risk of hazards during work. Cleaning service occupation becomes a job which often intersects with biological, ergonomic, physical, chemical and psychological hazards. If these hazards are not handled properly, they can cause work accidents, illness and even fatality. Identifying hazards at work is the initial stage before conducting risk assessment and mapping. The study aims to map the level of risk  in the cleaning service occupation. The study used a quantitative analytical method with an observational approach. Data was collected by doing observation and filling out Hazard Identification Risk Assessment (HIRA) form. The result reveals several levels of risk appearing in the risk matrix for cleaning service employees. Most of the risk matrix levels seen in the cleaning service occupation are "high risk", and "moderate risk" appears in a small percentage. According to the result, the recommended actions are controlling the hazard through repairing work tools followingthe physiology of cleaning service workers, providing periodic recess on each work shift, socializing regarding the nature and types of materials and how to handle chemicals properly, and providing appropriate PPE facilities for the type of activity occupation.